THE EUROPEAN UNION, RUSSIA AND THE GEORGIA – ABKHAZIA CONFLICT (1992 – 2015) - O. S. Samutina; K. V. Yumatov (Вестник Кемеровского государственного университета, 2015)
The collapse of the USSR led to a number of military and political conflicts emerging in the post-Soviet area. The conflict between Georgia, South Ossetia and Abkhazia triggered the factor of the EU, Russia and the USA influencing the international relations in the South Caucasus. Since August 2008, the EU has found itself directly involved in the Ossetia-Georgia, GeorgiaAbkhazia and RussiaGeorgia conflicts. The EU influence on Georgia allows, on the one hand, restricting the Georgian authorities from the military solution of the conflict, and on the other hand, creating the image of Georgia as a country seeking for political dialogue and opposing the Russian expansion plans in the South Caucasus. The creation and activities of the European Union Monitoring Mission provided Georgia with a foreign policy cover from the possible military and political pressure from the rebelling ―autonomies‖ and the Russian federation supporting them. Abkhazia‘s refusal to accept the EUMM for permanent work in the territory of the un-recognized republic was seen by the EU as Russia‘s and Abkhazia‘s authorities refusal to facilitate the solution of the conflict in the political way. Thus, the EU actions can be regarded not only as real peace-making activities, but rather an aspect of political struggle for authority in the South Caucasus and in the postSoviet area